2012
DOI: 10.1093/deafed/ens022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Distinguishing Skilled and Less Skilled Deaf Readers: Evidence From Four Orthographies

Abstract: This study aims to enhance understanding of the factors underlying variance in the reading comprehension skills of prelingually deaf individuals. Participants were 213 sixth through tenth graders with prelingual deafness recruited from four orthographic backgrounds (Hebrew, Arabic, English, and German) and allocated to three distinct reading profiles (levels). A sentence comprehension test manipulating the semantic plausibility of sentences and a word processing experiment requiring rapid determination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 59 publications
0
17
0
4
Order By: Relevance
“…This causes their ASL phonological skills to remain weak and nonnative despite having many years to develop abilities in ASL. Furthermore, deaf signers from deaf parents are more than twice as likely to be skilled readers than deaf signers from hearing parents . Together, this predicts that late exposed signers will have weaker reading skills than early signers because their weaker phonological segmentation abilities impede reading processes.…”
Section: Modelmentioning
confidence: 99%
“…This causes their ASL phonological skills to remain weak and nonnative despite having many years to develop abilities in ASL. Furthermore, deaf signers from deaf parents are more than twice as likely to be skilled readers than deaf signers from hearing parents . Together, this predicts that late exposed signers will have weaker reading skills than early signers because their weaker phonological segmentation abilities impede reading processes.…”
Section: Modelmentioning
confidence: 99%
“…Good ASL skills correlate with L2 reading comprehension (Chamberlain & Mayberry, 2000;Hermans, Ormel, & Knoors, 2010;Hoffmeister, 2000;Lichtenstein, 1998;Miller et al, 2012;Strong & Prinz, 1997). A growing literature examines how ability in vocabulary, syntax, and phonology influences reading comprehension, as described in the next section.…”
Section: The Relationship Between Language Knowledge In a L1 And Readmentioning
confidence: 99%
“…Syntactic knowledge also predicts reading comprehension (Chamberlain & Mayberry, 2008;Miller et al, 2012). For example, Chamberlain and Mayberry (2008) found that skilled deaf adult readers of English scored higher on a test of ASL syntax.…”
Section: Syntactic Knowledgementioning
confidence: 99%
See 2 more Smart Citations